2018
DOI: 10.3390/ijms19082278
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Melatonin Administration Is Crucial for Its Antidepressant-Like Effect in Mice

Abstract: Melatonin is synthesized by the pineal gland with a circadian rhythm in synchrony with the environmental light/dark cycle. A gradual increase in circulating levels of melatonin occur after lights off, reaching its maximum around the middle of the dark phase. Agonists of melatonin receptors have proved effectiveness as antidepressants in clinical trials. However, there is contradictory evidence about the potential antidepressant effect of melatonin itself. Herein we studied melatonin administration in mice at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 59 publications
0
14
0
1
Order By: Relevance
“…To examine whether the KET/MEL combination would be more effective than either drug alone in reducing the immobility behavior, we administered sub-effective doses of KET (1.5 mg/kg) and MEL (4 or 16 mg/kg, i.p.) simultaneously, 30 min before the FST [15]. KET at 1.5 mg/kg did not reduce the immobility time in mice summited to the FST (Figure 1A).…”
Section: The Combination Of Ketamine and Melatonin At Sub-effective Doses Induced Antidepressant-like Effects After A Single Administratimentioning
confidence: 89%
See 3 more Smart Citations
“…To examine whether the KET/MEL combination would be more effective than either drug alone in reducing the immobility behavior, we administered sub-effective doses of KET (1.5 mg/kg) and MEL (4 or 16 mg/kg, i.p.) simultaneously, 30 min before the FST [15]. KET at 1.5 mg/kg did not reduce the immobility time in mice summited to the FST (Figure 1A).…”
Section: The Combination Of Ketamine and Melatonin At Sub-effective Doses Induced Antidepressant-like Effects After A Single Administratimentioning
confidence: 89%
“…In addition, we have previously shown that a single administration of MEL (4 or 16 mg/kg i.p.) 30 min before the FST does not reduce the immobility time in this test [15]. To examine whether the KET/MEL combination would be more effective than either drug alone in reducing the immobility behavior, we administered sub-effective doses of KET (1.5 mg/kg) and MEL (4 or 16 mg/kg, i.p.)…”
Section: The Combination Of Ketamine and Melatonin At Sub-effective Doses Induced Antidepressant-like Effects After A Single Administratimentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from nuclear magnetic resonance-based studies and ligand-binding assays have shown that MEL can bind to Ca 2+ -CaM [ 10 , 16 , 17 ]. Exogenous MEL antidepressant-like effects in mice have been recently described [ 25 , 26 ], and modulation of neuroplasticity may underlie this effect. CaMKII plays a key role in neurogenesis and dendritogenesis which are processes stimulated by antidepressants and MEL [ 27 ].…”
Section: Discussionmentioning
confidence: 99%